A new prenatal sonographic sign of epidermolysis bullosa. Issue 1 (16th September 2020) - Chen, Daniela; Zuckerman, Shachar; Akerman, Yehudit; Shen, Ori
Abstract: We report on the prenatal sonographic appearance of epidermolysis bullosa (EB). The third viable pregnancy of a consanguineous couple was found at 23 weeks to have dysplastic external ears and nose. The neonate was born at 33 weeks and was found to have junctional EB with pyloric atresia. On reviewing the 23‐week ultrasound images, skin denudation was evident. This is a report of visualization of skin denudation in EB. When EB is suspected prenatally, special attention should be given to the visualization of skin surfaces.